Eigenfunctions and asymptotic behavior of Eigenvalues to the given boundary value problem with Eigenparameter in the boundary conditions - Mohammed, Aryan Ali (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this work, we derived the general solution for nth order linear ordinary differential equations of the form for and are continuous functions of via the method of variation of parameters. Likewise we found the eigenfunctions for the given second boundary value problem [1]-[3] as well as the boundedness of eigenfunctions, and the sign of real part of the eigenvalues have been specified through the sign of one parameter in the boundary conditions. Finally, the asymptotic behavior of eigenvalues to the given problem was studied.
Keywords: Eigenparameters; eigenfunctions; boundary conditions; asymptotic behavior